(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
In this article, the reaction of 5-acetyl-2-methyl-1-thiaindan molecule with benzaldehyde, propion aldehyde, oil aldehyde and isovalerian aldehyde as a substrate in aldol condensation reactions of bicyclic sulfur organic compounds is studied. According to the result of the reaction, the reaction of 5-acetyl-2-methyl-1-thiaindan molecule with various aldehydes proceeds in the same way as aliphatic aldehyde and ketones, and the yield of the reaction product is high.